Current status of psychiatric care in Thailand - Kamonporn Wannarit; Panate Pukrittayakamee; Pichet Udomratn (Taiwanese Journal of Psychiatry, 2023)
Background: Psychiatric care in Thailand has been established for a long time. It started with Thai traditional medicine and care, and later, it has been integrated with Western knowledge. In this review, the authors intended to highlight how clinical services and training in Thailand have been adjusted in regard to a changing society, environment, and the world. Methods: The authors collected information from the literature relevant to psychiatric care in Thailand, including organizations in charge of the mental well-being of health-care professionals and the general public, prescribing patterns of psychotropic drugs, psychotherapy, other interventions, and gender diversity issues. Results: Psychiatric care in Thailand is consistently improving in collaborating and networking among organizations and societies to unite psychiatrists with common interests. New specialty and sub-specialty trainings are also offered in response to the demands of residents and fellows as well as patients. There are also more training centers in the central and regional areas of Thailand. Adjusting and strategically managing psychiatric care have been done to deal with service disruption from the COVID-19 pandemic. Interventions, including pharmacological management, different types of psychotherapy, repetitive transcranial magnetic stimulation, and electroconvulsive therapy, have combined with Western knowledge and Eastern wisdom to deliver appropriate approaches for Thai people, including mental health care for patients with gender diversity. But the health security system and access to mental health care are areas are still needed to be further improved. Conclusion: Over the decades since mental health care has been recognized and increasingly aware, there are improvements in clinical services and academic training. The implementation of those services is still required to be monitored and improved for all populations in Thailand without discrimination.